The efficacy of calorimetry-based nutritional support versus recommended dietary intake-based nutritional support in the successful weaning of chronically ventilated patients: A study protocol for a double blind randomized controlled trial. (April 2023) - Fradkin, Mila; Elyashiv, Maya; Brik, Michael; Kait, Michal G.; Albukrek, Dov; Singer, Pierre; Dankner, Rachel
Summary: Background & aims: Mechanically ventilated patients are weaned during acute care hospitalization when it is determined that they are ready for withdrawal. If weaning fails, patients are admitted to a rehabilitation medical center for continued supportive care and additional weaning attempts. This study's objective is to increase the success rate of weaning from prolonged mechanical ventilation (PMV), and to shorten the overall weaning period by tailoring the patient's caloric intake according to their individually measured energy needs. Methods: We designed a randomized, controlled, double-blinded trial to be conducted among PMV patients undergoing routine ventilation-weaning attempts. Patients in the intervention arm will be fed according to energy needs determined by calorimetry. Patients in the control arm will be fed according to the standard of care, namely the Recommended Dietary Allowance (RDA) guidelines. Each patient will undergo up to five weaning attempts. Study outcomes will include successful weaning rate, time to successful weaning, and 3–12 months survival rate. Discussion: This trial aims to examine the safety and efficacy of a nutritional diet based on an individual's measured caloric needs in terms of weaning rates and weaning time. We hypothesize that calorimetry-based nutrition plan will prove to be superior in both success rate and time to successful weaning compared to the standard nutrition plan based on the resting energy expenditure (REE) formula during the weaning process. Trial registration: ClinicalTrials.gov identifier: NCT04825717.